Clinical impact of a high-frequency seizure onset zone in a case of bitemporal epilepsy - Jiruška, Přemysl; Tomášek, Martin; Netuka, David; Otahal, Jakub; Jefferys, John G. R; Li, Xiaoli; Marusič, Petr (Epileptic disorders, 2008)
High-frequency activity has been described as having a role in the initiation of epileptic seizures. The case of a patient with refractory bitemporal epilepsy is presented. Extraoperative monitoring with depth and subdural electrodes revealed an ictal pattern with a build-up of high-frequency (> 80 Hz) activity originating in the cortex, with spread to both hippocampi. This observation was only revealed with the use of high-pass filtering, and represented crucial information that significantly influenced the decision about the side, localization and extent of resection. Removal of the cortex generating high-frequency activity, led to cessation of seizures in this patient. Current knowledge about the role of high-frequency activity and the case presented here support the importance of recording with equipment capable of detecting fast activity during the presurgical invasive monitoring. An active search for a high-frequency seizure onset zone in patients with structurally-unaffected hippocampi may improve the outcome beyond that possible with conventional bandwidth, invasive EEG recordings.
Keywords: implantované elektrody; Magnetic Resonance Imaging; magnetická rezonanční tomografie; Humans; lidé středního věku; epilepsie temporálního laloku; Neurosurgical Procedures; Female; Temporal Lobe; spánkový lalok; Hippocampus; lidé; elektroencefalografie; hipokampus; mozková kůra; Cerebral Cortex; Electrodes, Implanted; ženské pohlaví; Middle Aged; Epilepsy, Temporal Lobe; Positron-Emission Tomography; Electroencephalography; pozitronová emisní tomografie; neurochirurgické výkony